Brain glutamine synthetase alterations during experimental acute liver failure - Shulyatnikova, T. V.; Шулятнікова, Тетяна Володимирівна (Запорізький державний медичний університет, 2022)
The aim of the study was to determine the immunohistochemical level of glutamine synthetase (GS) expression in different brain regions in the conditions of experimental acute liver failure in rats.